2008
DOI: 10.1002/chem.200800052
|View full text |Cite
|
Sign up to set email alerts
|

The Phenoxy/Phenol/Copper Cation: A Minimalistic Model of Bonding Relations in Active Centers of Mononuclear Copper Enzymes

Abstract: The "bare" complex [Cu(PhOH)(PhO)](+) with a phenol (PhOH) and a phenoxy (PhO) ligand bound to copper is studied both experimentally and computationally. The binding energies and structure of this complex are probed by mass spectrometry, infrared multi-photon dissociation, and DFT calculations. Further, the monoligated complexes [Cu(PhO)](+) and [Cu(PhOH)](+) are investigated for comparison. DFT calculations on the [Cu(PhOH)(PhO)](+) complex predict that a phenolate anion interacts with copper(II) preferential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 95 publications
4
48
0
Order By: Relevance
“…Relative abundances of fragment ions display an energy dependence that can be modeled by a sigmoid function and phenomenological appearance energies may be derived from linear extrapolation of the rise of the sigmoid curves to the baseline. [65,[70][71][72] The curves were found not to be affected to any significant degree by varying the pressure in q2 (1.5-5.5 10 À5 mbar), which suggests that the CID experiments are not perturbed by multiple collision events.…”
Section: Methodsmentioning
confidence: 80%
“…Relative abundances of fragment ions display an energy dependence that can be modeled by a sigmoid function and phenomenological appearance energies may be derived from linear extrapolation of the rise of the sigmoid curves to the baseline. [65,[70][71][72] The curves were found not to be affected to any significant degree by varying the pressure in q2 (1.5-5.5 10 À5 mbar), which suggests that the CID experiments are not perturbed by multiple collision events.…”
Section: Methodsmentioning
confidence: 80%
“…In this case, tyrosine takes an active role in the electron-transfer processes and is present as a radical, which can serve as an electron shuttle. The investigation of bonding relations between copper and phenolate, as a model for tyrosinate, revealed that phenolate interacts with copper via the oxygen atom, as expected [166][167][168][169]. Interestingly, the gas-phase study shows that the formation of the Cu O bond is associated with electron transfer from phenolate to copper so that the resulting complex (PhO)Cu + corresponds to copper(I) bound to the phenoxy radical [166,170].…”
Section: Case Study Ii: Interaction Of Copper(ii) With Phenolatesmentioning
confidence: 92%
“…Interesting to note in this context is that the bonding between copper(I) and neutral phenol moiety does not take place via the oxygen atom, but copper is rather bound to the aromatic ring [176][177][178][179][180]. This remarkable feature was proved by calculations using density functional theory and infrared multiphoton dissociation (IRMPD) spectra of mass-selected ions [166], where the combination of these two modern techniques which is one of the most powerful tool available for the structural elucidation of gaseous ions [15,[181][182][183][184].…”
Section: Methodsmentioning
confidence: 98%
“…Moreover, recent calculations performed for various isomers of [Cu(PhOH)] + did not reveal severe discrepancies with the results obtained at the DFT and CCSD(T) levels. [27] As far as the reaction mechanism is concerned, we checked (for 1a) our previous suggestion that a pentacoordinate silicon intermediate of type B or a copper(III) intermediate like C might be involved (Scheme 4). We did not succeed in optimizing such intermediates.…”
Section: Theoretical Studiesmentioning
confidence: 99%